EDUPRENEURSHIP: MANFAAT VIDEO PEMBELAJARAN MATEMATIKA PADA PLATFORM YOUTUBE - ray leonard januar; Ishaq Nuriadin2 (STKIP Andi Matappa, 2024)
This research aims to observe and determine the benefits of implementing mathematics learning videos on the YouTube platform. This research is included in the type of descriptive qualitative research. The data collection method used in this research was a questionnaire given to class VIII students. The sample in this study was taken as many as thirty students. The data source in this research is the results of questionnaires that have been filled out by students. Before the questionnaire is given to students, the questionnaire is tested for validity and reliability first and the results show that the questionnaire is valid and reliable. Questionnaires were distributed to students after students watched mathematics learning videos on the given YouTube platform. Data is processed through stages 1) data examination, 2) classification, 3) verification, 4) analysis, 5) drawing conclusions. The results of this research show that learning videos on the YouTube platform are effective in helping students learn mathematics, and YouTube videos can help overcome students' difficulties in understanding, and YouTube videos can be useful for training students' mathematical problem solving abilities.